Upper Jurassic of the Barrow sub-basin: sedimentology, sequence stratigraphy and implications for reservoir development - Wulff, Keiran (Curtin University, 1991)
A chronostratigraphic subdivision of the Upper Jurassic synrift sediments in the eastern Barrow Sub-basin was developed from the integration of core logging, petrography, well log sequence analyses and seismic stratigraphy. From this basis, the Callovian to base Cretaceous sediments may be subdivided into five depositional sequences. The development of the sequence boundaries, in most part, is closely related to periods of major changes in basin configuration associated with the sequential breakup of eastern Gondwanaland. Initiation of the Upper Jurassic rift complex occurred during late Callovian early Oxfordian associated with the development of a northeast-southwest trending spreading centre on the Argo Abyssal Plain. The spreading centre propagated southwards during the Late Jurassic. This resulted in active rifting in the Barrow Sub-basin and ultimately led to the separation of the Indian and Australian plates during Valanginian time.Upper Jurassic synrift sediments in the eastern Barrow Sub-basin consist of detached basin floor fan complexes, channelised and canyon fed fan systems, slump deposits, prograding outer shelfal to slope deposits and deep marine claystones. Post-depositional uplift of the eastern shelfal areas during the Late Jurassic resulted in erosion of the transgressive and highstand fluvial-deltaic to shelfal deposits. These periods of uplift and erosion provided much of the sediment redeposited in the basinal areas during the lowstand periods. Seven sandstone facies were recognised in the Upper Jurassic sedimentary section based on core control. Each sandstone has unique reservoir characteristics which can be related to the depositional setting.The abundance of glauconite and belemnites combined with ichnology and biostratigraphic assemblages associated with marine environments, indicate that deposition of all the sandstone facies occurred within an outer shelfal - deep marine environment. Reservoir quality was best developed in the dominantly medium grained, moderate - well sorted sandstones, (facies 7), which were deposited as detached, basin floor submarine fan sands or interbedded turbidites. In contrast, reservoir quality was relatively poorly developed in the remaining facies which were deposited as slope fans, slumps, or distal turbidite deposits.The abundance of quartz and presence of banded iron, jasper, and potassic feldspar grains support the provenance for the basinal sandstone facies being the Precambrian alkyl granites and banded iron formation of.the Pilbara Shield and Hammersley Ranges. These Precambrian igneous rocks and metasediments mark the eastern boundary of the Barrow Sub-basin study area. To predict the distribution of sedimentary facies in the Upper Jurassic synrift sediments of the eastern Barrow Sub-basin, the interplay between the major controlling depositional processes, namely tectonics, sediment supply and eustasy must be understood. Subdivision of the synrift sedimentary section on the basis of lithostratigraphy can be misleading and does not adequately resolve the facies relationships observed in the well intersection. The results of this research form the basis for a regional sequence analysis and seismic stratigraphic study.